Analysis of Coverage of Visit to the Integrated Toddler Service Post in the New Normal Era of the COVID-19 Pandemic at the Sedinginan Public Health Center, Tanah Putih District, Rokan Hilir Regency, 2022 - Wenny Indriani; Yessi Harnani; Nurvi Susanti (Budapest International Research and Critics University, 2022)
The purpose of this research is to find out analysis of coverage of visit to the integrated toddler service post in the new normal era of the coronavirus disease 2019 (COVID-19) pandemic at the Sedinginan Public Health Center, Tanah Putih District, Rokan Hilir Regency, 2022. This type of research is qualitative research with a phenomenological approach. The location of this research is carried out at the Sedinginan Public Health Center, Tanah Putih District, Rokan Hilir Regency. While the time of the study was carried out in May-June 2022. The informant selection technique is using purposive sampling. The stages of data processing consist of data source triangulation, triangulation method, and data triangulation. Based on the results of observations, it is known that there is a government policy regarding the implementation of Integrated Service Post during the COVID-19 pandemic as stated in the guidebook for under-five health services during the COVID-19 emergency response period published by the Ministry of Health of the Republic of Indonesia in 2020. The facilities and infrastructure at the Integrated Service Post are complete but there are still Integrated Service Post that do not have their own buildings. Public Health Center are involved in providing vaccines and monitoring activities. The phenomenon of low community participation in Integrated Service Post activities cannot be resolved without cooperation with related parties. All parties have made maximum efforts in providing information including through social media such as facebook and whatsapp but there are still low visits to the Integrated Service Post. The budget for the implementation of the Integrated Service Post, which came from two parties, is currently not sufficient to finance all activities at the Integrated Service Post such as adding children's play facilities, giving rewards to toddlers who routinely weigh in the Integrated Service Post as well as making extension support tools.